2022
DOI: 10.21059/buletinpeternak.v46i2.71993
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Sawdust as Carbon Sources in Rabbit Manure Compost for Increasing the Growth of Pennisetum purpureum cv Mott

Abstract: The right proportion of carbon in high N organic matter source in composting process will result good decomposition process. In this study rabbit manure was composted with different portion of sawdust, and then the chemical properties were evaluated. The compost then applied to reveal the growth response of dwarf elephant grass (Pennisetum purpureum cv. Mott) in terms of plant height, number of leaves, root and shoot dry matter, shoot and shoot ratio, and N content in shoot. The results showed that compost con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Dalam penelitian ini, kotoran ternak yang digunakan adalah kotoran ternak yang tidak tercampur dengan sisa pakan. Kemudian, kotoran ternak dikomposkan dengan menggunakan EM4 untuk mempercepat proses pengomposannya, karena mikroorganisme berperan penting dalam proses dekomposisi (Dianita et al, 2022). Sementara itu, banyak penelitian dengan menggunakan pupuk kotoran ternak, namun tidak dilakukan proses pengomposan terlebih dahulu.…”
Section: Rumputunclassified
“…Dalam penelitian ini, kotoran ternak yang digunakan adalah kotoran ternak yang tidak tercampur dengan sisa pakan. Kemudian, kotoran ternak dikomposkan dengan menggunakan EM4 untuk mempercepat proses pengomposannya, karena mikroorganisme berperan penting dalam proses dekomposisi (Dianita et al, 2022). Sementara itu, banyak penelitian dengan menggunakan pupuk kotoran ternak, namun tidak dilakukan proses pengomposan terlebih dahulu.…”
Section: Rumputunclassified
“…Most especially, rabbit manure compost and vermicompost have been said to be cheap to produce and can be used as organic fertilizer to increase the quantity and quality of the crops produced. It has been proved that rabbit manure contains high amounts of nitrogen (Dianita et al, 2022), high phosphorus and potassium (Dixie, 2016), the amount of minerals that are sufficient to ameliorate the deficient quantities in the soil. More so, rabbit pellets do not pose threat to plants when applied; they have also been found to contain good levels of beneficial micro-elements.…”
Section: Innovations For Sustainable Food Systemsmentioning
confidence: 99%
“…Most importantly, rabbit compost tea and vermicompost, which are easy to make from rabbit manure, can be utilized as organic fertilizers to boost crop yields and quality. Dianita et al (2022) found out that rabbit manure contains high levels of nitrogen. According to Dixie (2016) and Adi et al (2020), fresh rabbit manure is a well-balanced fertilizer that contains roughly 2% nitrogen, 1% potassium, and 1% phosphorus; however, Minnich (2005) confirmed that fresh rabbit manure has 1.4% phosphorus, 2.4% nitrogen, and 0.6% potassium and also has the highest nitrogen content compared to other livestock manures.…”
Section: Introductionmentioning
confidence: 99%